Metabolic engineering of functional phytochemicals - Umar, Kabir Mustapha; Mohammed, Abdulkarim Sabo; Radu, Son; Abdul Hamid, Azizah; Saari, Nazamid (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
Phytochemicals belonging to the group’s phenols, terpenes, betalains, organosulfides, indoles and protein inhibitors are important components in fruits, vegetables, legumes, whole grains and nuts that have health promoting benefits and a variety of applications in food and pharmaceutical industries. Initially only a few of these important phytochemicals are produced commercially by chemical synthesis. However, recent developments in the field of biotechnology have provided metabolic engineering strategies that use microorganisms as cell factories for high production of these products. This review will discuss the general biosynthetic pathways, metabolic engineering and optimization strategies of functional phytochemicals that have received a lot of attention from investigators.